IMPLYING CYBERSECURITY SKILLS FOR PUBLIC ADMINISTRATION EMPLOYEES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The results of a conducted study on the knowledge and skills of representatives of the public and local administration regarding cyber security in modern digital work processes are presented. The survey was conducted in 2023 in the Republic of Bulgaria. The analysis includes a comparison of the data with those of a similar survey of employees in the public administration in 2020.